REVITALISASI PENGELOLAAN KEUANGAN UNTUK MENINGKATKAN AKUNTABILITAS PELAPORAN BUMDESA MUTIARA BUMI - Faisol, Moh; Norsain (Universitas Muhammadiyah Malang, 2022)
The Financial Management for BUMDesa is vital for management and interested parties so that the preparation of financial reports is a must. The main problem that exists in Mutiara Bumi BUMDesa is financial management, in the absence of financial reports that comply with standards. For this reason, this service is carried out by offering a solution in the form of an accounting bookkeeping system with MS. Excel and an accurate serial number of evidence. The problem-solving method will be carried out in stages (1) compiling the BUMDesa financial report module; (2) training on the preparation of BUMDesa financial reports; and (3) Evaluation and mentoring. The result of this service is that Mutiara Bumi BUMDesa is able to compile financial statements for 2020, which include a Profit and Loss Statement, a Statement of Changes in Capital, a Statement of Financial Position, and a Cash Flow Statement and a List of Accounts. This activity received appreciation from the Head of BUMDes Mutiara Bumi because it was useful in compiling computerized financial reports with MS. Excel. In addition, the tenacity of the service team in assisting and providing understanding related to the preparation of financial reports using MS. Excel.